2019
DOI: 10.1016/j.ebiom.2019.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the tyrosine phosphatase SHP-2 drives vascular dysfunction in Sepsis

Abstract: Background Sepsis, the most severe form of infection, involves endothelial dysfunction which contributes to organ failure. To improve therapeutic prospects, elucidation of molecular mechanisms underlying endothelial vascular failure is of essence. Methods Polymicrobial contamination induced sepsis mouse model and primary endothelial cells incubated with sepsis serum were used to study SHP-2 in sepsis-induced endothelial inflammation. SHP-2 activity was assessed by depho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…Inhibition of SHP2 was suggested to enhance leukocyte-endothelial adhesion, but impair the diapedesis process (Yan et al, 2017). In line with the former result, SHP2 was found to become inactivated in sepsis which supported IL-1β induced NFkB-driven pro-inflammatory transcriptional activity and enhanced expression of ICAM-1 and VCAM-1 (Heun et al, 2019). Thus, SHP2 regulates multiple signaling mechanisms in endothelial cells which affect inflammatory processes in different ways.…”
Section: Discussionsupporting
confidence: 55%
“…Inhibition of SHP2 was suggested to enhance leukocyte-endothelial adhesion, but impair the diapedesis process (Yan et al, 2017). In line with the former result, SHP2 was found to become inactivated in sepsis which supported IL-1β induced NFkB-driven pro-inflammatory transcriptional activity and enhanced expression of ICAM-1 and VCAM-1 (Heun et al, 2019). Thus, SHP2 regulates multiple signaling mechanisms in endothelial cells which affect inflammatory processes in different ways.…”
Section: Discussionsupporting
confidence: 55%
“…Western blot analysis further confirmed a significant elevation of TLR4 and Myd88 protein levels in TLR2-deficient offspring-pLPS, while the expression of phospho-MyD88 Tyr257 was proportionally increased when normalized to total Myd88 protein levels in the TLR2-deficient offspring-pLPS adipose tissue (Figure 5D), suggesting that the activation of MyD88 is at the transcriptional level. Since the phosphorylation of Myd88 at Tyr257 is likely involved in the recruitment of PI-3 kinase p85 subunit to Myd88 for further inflammatory signal transduction, our results suggest that this process might not be affected by the genetic compensation of TLR4 alone, however, our results highlight the potential hypersensitivity in TLR2-deficient offspring-pLPS to additional inflammatory stimulation (Gelman et al, 2006; Heun et al, 2019).…”
Section: Resultsmentioning
confidence: 74%
“…The inflammation status in cartilage or periarticular tissues is mostly attributed to MAPK and NF-κB pathways whose hyperactivation directly initiate and target articular cartilage and subchondral bone, causing cartilage degeneration and subchondral bone formation. Previous studies have shown SHP2 mediated MAPK and NF-κB activation (Zou et al, 2007;Heun et al, 2019;Niogret et al, 2019;Liu et al, 2020). However, whether SHP2 regulated these signaling in OA pathogenesis was not fully elucidated.…”
Section: Discussionmentioning
confidence: 99%